2002
DOI: 10.1016/s0002-9149(02)02203-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of dobutamine Tc-99m sestamibi-gated single-photon emission computed tomography for prediction of left ventricular ejection fraction outcome after coronary revascularization for ischemic cardiomyopathy

Abstract: Gated single-photon emission computed tomography (SPECT) imaging allows analysis of myocardial perfusion and assessment of baseline global and regional left ventricular (LV) function and their changes during lowdose dobutamine infusion. The study examined whether the changes in LV ejection fraction induced by dobutamine and evaluated using technetium-99m sestamibigated SPECT predict the evolution of ejection fraction after revascularization in patients with ischemic cardiomyopathy. Thirty-seven patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…The reaction to low-dose dobutamine can be predictive of the left ventricular functional response to revascularisation. Our group observed that an ejection fraction increase by ≥5 units during dobutamine predicted an increase of ≥5 units after revascularisation with an accuracy of 77%, a positive predictive value of 73% and a negative predictive value of 81% [111]. In patients with recent-onset idiopathic dilated cardiomyopathy, Kasama et al demonstrated that the ejection fraction changes induced by low-dose dobutamine and evaluated using gated SPECT were predictive of spontaneous improvement at 1-year follow-up [112].…”
Section: Gated Spect For the Assessment Of Contractile Reservementioning
confidence: 65%
“…The reaction to low-dose dobutamine can be predictive of the left ventricular functional response to revascularisation. Our group observed that an ejection fraction increase by ≥5 units during dobutamine predicted an increase of ≥5 units after revascularisation with an accuracy of 77%, a positive predictive value of 73% and a negative predictive value of 81% [111]. In patients with recent-onset idiopathic dilated cardiomyopathy, Kasama et al demonstrated that the ejection fraction changes induced by low-dose dobutamine and evaluated using gated SPECT were predictive of spontaneous improvement at 1-year follow-up [112].…”
Section: Gated Spect For the Assessment Of Contractile Reservementioning
confidence: 65%
“…Recently, the simultaneous assessment of myocardial cellular integrity using perfusion imaging and of contractile reserve using dobutamine gated SPECT has been suggested as a new approach to viability detection [18][19][20][21]. Various studies demonstrated that the combination of perfusion quantification and contractile reserve evaluation achieved results that were significantly superior to perfusion or contractile reserve data applied separately.…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc sestamibi gated SPECT is a novel and interesting method for identifying myocardial viability because, in a single stress study, it can provide information about the degree of regional asynergy, segmental tracer uptake, and regional contractile reserve, obviating the need for separate tests to assess reversible dysfunction. The addition of functional data to stress and rest perfusion images significantly improves their specificity and reduces the uncertainty in test interpretation, with a better separation of normal from abnormal studies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…, 1995), regional wall contraction by low‐dose dobutamine echography, gated SPECT and MRI (Qureshi et al. , 1997a,b; Leoncini et al. , 2002), regional or global perfusion and functional recovery, etc (Tillisch et al.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there have been a variety of end-points proposed for detecting the viability, including myocardium metabolism (Di Carli et al, 1994), biopsy followed by histological examination (Zimmermann et al, 1995), regional wall contraction by low-dose dobutamine echography, gated SPECT and MRI (Qureshi et al, 1997a,b;Leoncini et al, 2002), regional or global perfusion and functional recovery, etc (Tillisch et al, 1986;vom-Dahl et al, 1994;Udelson et al, 1994;Tamaki et al, 1995). From the clinical point of view, the improved perfusion and function following revascularization are optimal endpoints in viability studies, because these have been considered as the main goals of revascularization.…”
Section: Discussionmentioning
confidence: 99%